PCM assisted reverse electro discharge machining process for pattern generation. Issue 9 (4th July 2022) - Mazarbhuiya, Rashed Mustafa; Rahang, Maneswar
ABSTRACT: This research work reports about pattern generation using the photochemical machining (PCM) assisted reverse electro discharge machining (EDM) process on an aluminum 6061 workpiece. A mixture of fine powder of copper and tungsten is used to fabricate a green compact tool. A complex shape is generated onto the tool surface and is further implemented to migrate the shaped tool particle onto the work surface. The output parameters are the material deposition rate (MDR), tool wear rate (TWR), edge deviation (ED), and surface roughness (Ra). The pattern is characterized by Field Emission Scanning Electron Microscopy (FESEM) and Energy Disperse Spectroscopy (EDS) analyses. The presence of tungsten particles increases the microhardness of the substrate material. The surface microhardness of the pattern is found to be 362Hv.